PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR IPAS MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI KELAS IV SD NEGERI 169/IX MARGA - Fajar Prasetiawan; Indryani; Ugi Nugraha; Sulistyo, Urip (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is motivated by the low level of student activity and learning outcomes caused by the less than optimal learning process implemented. Some indications are that students do not understand the material taught so they tend to be passive, teacher-centered learning, have not used a variety of learning models and low student learning outcomes. This study uses the type of PTK research which is carried out in two cycles. Each cycle consists of two meetings. Each cycle consists of planning, implementation, observation and reflection. The purpose of this study is to describe the increase in activity and learning outcomes of science using the Problem Based Learning (PBL) learning model in class IV of SD Negeri 169/IX Marga. The subjects of this study were 29 fourth grade students. The data collection techniques used were tests and non-tests. Non-tests include observation and documentation. The data analysis techniques used were quantitative and qualitative. The results showed that there was an increase in student activity and learning outcomes using the Problem Based Learning learning model. This is evidenced by the increase in each cycle. The percentage of student activity in cycle 1 was 72.41% and increased in cycle 2 to 93.10%. The percentage of student learning outcomes completion in cycle I was 68.96% and increased in cycle II to 82.58%. The results of the data collection instrument have reached the criteria for successful action, therefore the action was stopped in cycle II.